Effect of Simulation-Based Training on Maternity Nurses' Performance and Self-Efficacy Regarding Management of Preeclampsia - Eman M. Abd Elhakam; Nour Elhoda M. Elshabory; Nabaweya S. Shehata (Evidence-Based Nursing Research)
Context: The use of simulation is one solution to the problem of integrating new care. New nurses must be competent to care for patients in a fast-paced setting where clinical competence and precise and timely decision-making are valued.